Acquired bullous epidermolysis: complexity of diagnostics - V. I. Al'banova; M. A. Nefedova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes the case of acquired bullous epidermolysis in a woman of 45 years old, suffering from a disease from 2.5 years. As a child, she was diagnosed with herpetiform dermatitis on the base of a clinical picture and histological data. After the period of puberty, when in addition to skin blistering a lesion of the oral mucosa, dystrophy and absence of nail plates, contracture of the 2 fingers of the hands arose, the diagnosis was changed to dystrophic congenital bullous epidermolysis, which did not contradict with re-histological examination of the skin. In order to clarify the diagnosis, another biopsy of the leg skin was performed in 2016. The light microscopy data corresponded to the herpetiform dermatitis or vesicular form of the bullous pemphigoid, the acquired bullous epidermolysis was not also excluded. Indirect RIF allowed to reject the diagnosis of herpetiform dermatitis. The possibility of bullous pemphigoid developing on the background of preexisting congenital bullous epidermolysis was investigated by immunofluorescence mapping with antibodies to 13 structural proteins of the dermo-epidermal junction. Expression of all the studied proteins corresponded to that of healthy individuals, which conflicted with the diagnosis of congenital bullous epidermolysis. Additional immunofluorescence study of the sites of spontaneous cleavage of the biopsy specimen, as well as of n- and u-patterns in the structure of the luminescence line, made possible to exclude the bullous pemphigoid. So, the use of a complex of immunomorphological methods helped to establish the correct diagnosis.